The Ability of the Raccoon Tail Water Plant (Ceratophyllum demersum) as a Biocathode in the Plant-Microbial Fuel Cell System - Saharuddin, Sahrani; Febryanti, Amalyah; Azis, Fitria (Jurnal Sumberdaya Alam dan Lingkungan, 2024)
ABSTRACT Plant-Microbial Fuel Cell (P-MFC) is a green technology because it uses a biocathode in the cathode compartment and also uses microorganisms to break down the chemical energy of organic matter into electrical energy. In this research, molasses and Saccharomyces cereviceae were used as substrates and Ceratophyllum demersum as a biocathode in the cathode compartment. The purpose of this study was to determine the potential variation in plant weight of C. demersum as a biocathode in the P-MFC system. The results of this study indicated that the maximum current at the biocathode was at a weight of 70 g, namely 0.180 mA with a power density value of 13.664 mW.m-2 and the maximum potential difference at the biocathode was at a weight of 40 g, which as 0.310 mV with a power density value of 30.787 mW.m-2. Therefore, coontail water plant has the potential as biocathode. Keywords:  biochatode, molasses, P-MFC, raccoon tail water, Saccharomyces cereviceae